2019
DOI: 10.1136/bmjspcare-2019-001823
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement support effectiveness for parents of infants and children: a systematic review

Abstract: ObjectivesThis systematic review aims to assess the effectiveness of bereavement support interventions (BSIs) for parents of an infant or a child who has died from a medical condition or in unforeseen circumstances.MethodsA systematic search of MEDLINE, PsycINFO, Embase and CINAHL (1980 to January 2018) was performed to identify studies investigating BSIs for the parents of children who died between the ages of 24 weeks gestation and 30 years. Due to significant clinical and methodological heterogeneity betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Once again, they concluded that the lack of rigorous evidence precluded any formal recommendation about interventions for bereaved parents. Most recently, in 2019, another systematic review by Ainscough et al also looked at the effectiveness of bereavement support for parents of infants and children [33]. Of the 24,556 records assessed, 9 articles met the inclusion criteria.…”
Section: Supportive Interventionsmentioning
confidence: 99%
“…Once again, they concluded that the lack of rigorous evidence precluded any formal recommendation about interventions for bereaved parents. Most recently, in 2019, another systematic review by Ainscough et al also looked at the effectiveness of bereavement support for parents of infants and children [33]. Of the 24,556 records assessed, 9 articles met the inclusion criteria.…”
Section: Supportive Interventionsmentioning
confidence: 99%
“…9 A range of interventions for bereaved parents exist including pharmacotherapy, counseling, psychotherapy, and systems-oriented interventions. [10][11][12][13][14] However, studies involving bereaved parents identified additional sources of support requested by parents and families. [15][16][17] These services included structured bereavement support, mailings, memorial events, and support groups.…”
Section: Introductionmentioning
confidence: 99%
“…A range of interventions for bereaved parents exist including pharmacotherapy, counseling, psychotherapy, and systems‐oriented interventions 10‐14 . However, studies involving bereaved parents identified additional sources of support requested by parents and families 15‐17 .…”
Section: Introductionmentioning
confidence: 99%
“…5,14 Other systematic reviews have focused on the effectiveness of formal bereavement interventions by professionals which essentially found a lack of clarity about which formal support/services are useful due to significant research issues. 15,16 The aim of this scoping review is to clarify from the standpoint of bereaved parents what are considered helpful and unhelpful characteristics of informal support given by the support network of bereaved parents.…”
Section: Introductionmentioning
confidence: 99%